2010
DOI: 10.1111/j.1471-0307.2010.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of Civil cheese: a type of traditional Turkish cheese

Abstract: Civil cheeses were purchased from urban vendors in the city centre of Erzurum, Turkey. The biogenic amine contents of the cheeses and their microbiological and chemical properties were determined. It was found out that biogenic amine concentrations of the samples were not exceeding the toxic doses-values. Total aerobic mesophilic bacteria, lactic acid bacteria and Enterobacteriaceae spp. were investigated as microbial analyses in the samples while several chemical analyses were executed. Statistical analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
3
3
1
1
Order By: Relevance
“…() and Yildiz et al . () found an association between the putrescine content and the Enterobacteriaceae count, which is in agreement with that found in this study, in which the M3 brand has the highest count.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…() and Yildiz et al . () found an association between the putrescine content and the Enterobacteriaceae count, which is in agreement with that found in this study, in which the M3 brand has the highest count.…”
Section: Resultssupporting
confidence: 92%
“…Bunka et al (2012) showed values of between 11.2 and 459.8 for Dutch Gouda at the beginning and end (90 days) of ripening, respectively. Marino et al (2000), Martuscelli et al (2005) and Yildiz et al (2010) found an association between the putrescine content and the Enterobacteriaceae count, which is in agreement with that found in this study, in which the M3 brand has the highest count.…”
Section: Analysis Of Biogenic Aminessupporting
confidence: 92%
“…Previous studies reported significant positive correlations between BAs and corresponding precursor amino acids (Kebary, El-Sonbaty, & Badawi, 1999;Pinho et al, 2004). On the contrary, no significant correlation was found between tyramine and tyrosine in traditional Turkish Civil cheese (Yildiz et al, 2010). These apparently conflicting results may be explained by the fact that availability of precursor amino acids is not a sufficient prerequisite for BA production, rather than needing the concurrent presence of decarboxylase-positive bacteria is.…”
Section: Discussioncontrasting
confidence: 47%
“…The author reported that histamine and tyramine were the predominant biogenic amines in cheeses regardless of variety. Yildiz et al () studied biogenic amine contents of Civil cheese collected from retails and they reported that all samples contained one or more different biogenic amines but their levels were not above specified toxic dose for public health. Aliakbarlu, Alizadeh, Razavi‐Rohani, and Agh () investigated the effects of processing factors such as ripening time (25–75 days), ripening temperature (4–14 °C), and brine concentration (10–13%) on biogenic amine content, proteolysis, and sensory scores of Iranian white brined cheese.…”
Section: Introductionmentioning
confidence: 99%